Penerapan Model Example Non Example Untuk Meningkatkan Hasil Belajar Siswa Kelas 5 MI Muhammadiyah Pabelan - Fina Fitriyati (Prosiding University Research Colloquium, 2021)
The purpose of this research is to omprove the student’s learning skills by applying theNon Example Learning Model. The research method used is Class Action Research (PTK)consisting of two cycles where each cycle has a planning, action, observation, and reflectionstage. This research involves seven fifth grade elementary students. Based on observationsand tests on cycle 1 there is an increase. The highest score after the treatment done oncycle 1 was 85 and the lowest score 71 with an average of 76.85. Whereas the initial resultswere the highest score is 75 and the lowest score is 60 with a flat rate of 66.57. While theresults at cycle stage 2 are 90 highest and 78 lowest with a flat rate of 82.28. The first halfof the score is the highest 80 and the lowest 70 with a flat 75.71. So it can be concludedthat the model learning Non-Example can increase student learning outcomes.